The functional diagram of quality of products management on mixed fodder enterprises - Тарас Ігорович Ткаченко (Tehnologìčnij Audit ta Rezervi Virobnictva, 2013)
The functional diagram of product quality management on mixed fodder enterprises is proposed in the paper. The method of activity analysis of mixed fodder enterprises, which allows to increase the product quality and to improve the competitiveness in the market environment, is proposed. Modern production level allows the transition to automated accounting of raw materials, semi-products and products during the whole production process. The bases for such accounting are usually industry standards or technological instructions, developed on the mixed fodder enterprise. Factors, listed above, as well as non-isomorphism of accompanying information flows allow to refer the automated accounting system in TP to the class of complex information systems, modeling and research of which requires a nonstandard approach that, in turn increases the quality management on the mixed fodder enterprise. The research results can be applied on the mixed fodder enterprises. The method of activity analysis of mixed fodder enterprises, which allows to increase the product quality and to improve competitiveness in the market environment, is proposed.